Unveiling the Link Between Brand Value and Firm Performance: A Systematic Literature Review - Naila, Muthia; Saiful Hakim, Muhammad (Journal of Accounting and Finance Management, 2025)
The question of how brand value contributes to firm performance has attracted growing attention, reflecting its strategic importance for both academia and business practice. A Systematic Literature Review (SLR) was conducted on 56 high quality peer-reviewed studies, based on Scopus database, to synthesize how this relationship has been conceptualized, measured, and interpreted across different context. Results show that the relationship is mostly positive, with 41,1% of studies reporting a direct effect and 30,4% identifying a context-dependent association, though outcomes vary by industry, firm size, financial condition, geography, and culture. Analysis of brand value measurement approaches reveals that nearly half of studies (46,4%) lack clear methodological articulation. Among the rest, financial-based dominate (30,4%), consumer-based approaches follow (21,4%), while hybrid models are rarely applied (1,8%). This imbalance highlights the majority of finance-driven perspectives and the underuse of integrative frameworks that could capture the multidimensional nature of brand value. This study offers a comprehensive synthesis of how measurement approaches and contextual moderators shape the brand value and firm performance link, also highlighting gaps for methodological and geographical expansion. The findings reaffirm brand value as strategic asset with concrete implications for competitiveness, financial outcome, and resilience.